Pengaruh Konflik Peran, Stres Kerja, dan Pemahaman Good Governance Terhadap Kinerja Auditor - Talise, Virginia Xena Francisca (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p18, 2019)
In order for auditors to have good performance, a company or Public Accountant Office needs to pay attention to the factors that influence the performance of its auditors. The purpose of this study is to examine and provide empirical evidence on the influence of role conflict, work stress and understanding good governance on auditor performance. This research was conducted at the Public Accounting Firm registered in the Directory published by the Indonesian Institute of Certified Public Accountants in 2018, which amounted to 8 offices with a sample of 60 auditors. Based on the results of the analysis it was found that role conflict partially had a negative and significant effect on auditor performance. Job stress partially does not affect auditor performance. Understanding of good governance partially has a positive and significant effect on auditor performance. Keywords : Role Conflict; Work Stress; Understanding Of Good Governance; Performance.